RAPID SCREENING OF ANTIBACTERIAL AND ANTIOXIDANT METABOLITES FROM ENDOPHYTIC FUNGI ISOLATED FROM Papuacedrus papuana BY TLC-BIOAUTOGRAPHY - Praptiwi Praptiwi; Muhammad Ilyas; Kartika Diah Palupi; Ahmad Fathoni; Evana Evana; Marlin Megalestin Raunsai; Andria Agusta (Balai Besar Kimia dan Kemasan, 2021)
Papuacedrus papuana is a rare plant that grows in highland of Papua. The in vitro antibacterial activity and antioxidant capacity of 17 endophytic fungal extracts isolated from P. papuana stem were investigated by TLC-bioautography. The antibacterial activity was assessed against Staphylococcus aureus InaCC B4 and Escherichia coli InaCC B5. The antioxidant capacity was assessed by DPPH radical scavenging assay. All of 17 endophytic fungi were grouped into 7 taxa based on their morphological traits. The results showed that 11 fungal extracts were active against S. aureus InaCC B4, 15 fungal extracts were active against E. coli InaCC B5 and 6 extracts had antioxidant activity. Further analysis of active extracts by eluted TLC-bioautography showed that there are several compounds responsible for antibacterial or antioxidant activity in one extract. The results showed that there is a diversity of endophytic fungi inhabited P. papuana stem and these endophytic fungi might be used as a good source of novel antibacterial or antioxidant.